Horticultural Plants and By-Products as Sources of Biological Active Compounds - Eliza Oprea; Ioana-Cristina Marinas; Mariana Carmen Chifiriuc (Horticulturae)
Horticultural plants and their by-products from vegetable, herb and fruit cultivation, as well as from food industry operations, warehouses, and retail trade, are abundant in biologically active compounds such as polyphenols, flavonoids, carotenoids, vitamins and minerals [...]